PENGENALAN PRODUK KEUANGAN SYARIAH PADA IBU-IBU PENGAJIAN MASJID FADHILAH RW 09 KELURAHAN, KECAMATAN LOWOKWARU KOTA MALANG - Muwidha Muwidha; Nur Indah; Mahmudatul Himmah; Suryadi Suryadi; Agustina Agustina (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
This community service activity is aimed at providing counseling and socialization to the community, especially the people who are members of the mosque as a place of spiritual interaction. In accordance with the purpose of a mosque that the mosque is not only for worship but also to gain knowledge about the completeness of muammalah in life.Implementation of activities as expected. The number of participants is 44 people of the father / mother of Lowokwaru Sub-District, Malang City. The participants' enthusiasm was quite good, this was observed carefully by the mothers in listening to the exposure of the material and the various questions raised. This sustainability is expected to be maintained. Given the awareness of the role of women in preparing their sons for the future. Participants hope the activities will continue with the same topic but with more practical studies.Reaching prosperity is a necessity because every soul has been equipped with glory and continues to strive for it for the life of the world and afterwards. Physical and immaterial needs are their size. Provision of fulfillment of the need for prosperity is a shared responsibility through the role of the government as a policy maker and the community as the object and actor. Islam has come with all the perfection of the concept. Islam provides a great benefit, because it is held by a trusted person.The contribution of Islamic economics to improving people's welfare should be a spirit in the implementation of Islamic economics in Indonesia. However, in reality this has not yet materialized, for example the practice of Islamic banking in Indonesia is still far from the concept.Community welfare is closely related to the principle of justice. If the principle of justice is truly implemented in Islamic economics, it will certainly be the right solution to reduce poverty, and in the end it will improve people's welfare based on togetherness.